NILAI-NILAI BUDAYA LOKAL DAN KEKERASAN TERHADAP PEREMPUAN MASA HAMIL-NIFAS DI KABUPATEN DONGGALA SULAWESI TENGAH - Rosmala Nur (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
This research is aim to study the local cultural forms which cause the domestic violence, especially on pregnancy woman. The research conducted in countryside of Sunju and Tg Batu, Donggala Middle Sulawesi district. The sample of the study is entire pregnancy women, and the women who were pregnancy two years ego. The total number of sample is 94 people. Data collecting are interview, focus group discussion, and documentation. The result of the research indicates that the value of local cultural namely siri', naeya, and doi' balanca as the cause